'It's not just to treat everybody the same': A social justice framework for caring for larger patients in healthcare practice. Issue 6 (17th April 2022) - Kanagasingam, Deana; Norman, Moss; Hurd, Laura
Abstract: Drawing on semi‐structured interviews with larger bodied patients ( n  = 20) and their healthcare practitioners ( n  = 22) in Canada, this paper combines micro and macro approaches in outlining a social justice approach to caring for larger patients in healthcare practice. Theoretically, we draw upon structural competency and critical consciousness to address the question of how social justice is enacted, experienced, and understood in interactions between clinicians and larger patients. Our findings highlight four key themes that provide a framework for integrating social justice into healthcare practice: (1) an awareness of one's simultaneous experience of marginalisation and privilege in the clinical interaction; (2) navigating between additive and interactive understandings of intersectionality; (3) micro and macro approaches to change; and (4) straddling the line between equity and equality. The synergies in participants' perspectives across social identities suggests that the cultivation of social justice awareness potentially mitigates some blinders of privilege. Furthermore, practitioners' social justice orientation positively impacted patient experience, with most patients expressing appreciation for having their various histories of trauma and social challenges handled compassionately during appointments.